Implementasi Pemanfaatan Botol Plastik sebagai Media Tanam di SMP Negeri 9 Pulau Soop: Penelitian - Ivonne M. Leiwakabessy; Novalien Syauta; Lili Sapari; Joni Penda; Denny Petta; Dormauli Br. Gultom; Dwi Indah Widya Yanti; Melisa Masengi; Disabella Dayera (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This community service program aimed to strengthen household food security on Pulau Soop by utilizing home yards and plastic bottles as planting media. The initiative addressed limited land availability and increasing plastic waste on the small island. Through training on converting plastic bottles into planting containers and cultivating vegetables at SMP Negeri 9 Pulau Soop, students gained knowledge and practical skills in recycling, appropriate technology, and simple cultivation methods. The results show improved student understanding, active participation, and the establishment of a school mini garden as an urban farming model. The program effectively supported environmental education, reduced plastic waste, and enhanced yard-based food security in the small island community.